„A Piccadilly Vénusza”: Város és identitás Angela Carter Esték a cirkuszban című regényében - Schäffer, Anett (Studia Litteraria, 2016)
In Angela Carter’s neo-Victorian novel Nights at the Circus we get to know London at the end of the 19th century. The protagonist of the story is Fevvers, a blonde winged aerialiste, whose life and identity are inseparable from London. In the beginning of the novel she tells the story of her life to a reporter, Walser, and starts the narrative by stating that she is a Londoner, the “Cockney Venus”. Fevvers’ life is connected to the capital city in many ways, and although the characters travel throughout most of the story, London plays an important role in the whole novel. Fevvers in her life embodies many important urban and non-urban female characters in the Victorian era showing how they function in the city: the prostitute, the angel in the house, the madwoman in the attic, the New Woman, the shopgirl, the flâneuse, and the object of the male gaze. In my paper I show how Fevvers embodies and questions the traditional female roles, how her identity changes throughout the novel and how London plays a key role in the formation of Fevvers’ identity as the only solid identifying point for her.